Compliance in Controlled E-cigarette Studies. Issue 3 (29th January 2020) - Rebuli, Meghan E; Liu, Feifei; Urman, Robert; Barrington-Trimis, Jessica L; Eckel, Sandrah P; McConnell, Rob; Jaspers, Ilona
Abstract: Introduction: E-cigarette studies have found that the use of a variety of flavors and customizable devices results in greater use frequency and user satisfaction. However, standardized research e-cigarettes are being developed as closed systems with limited flavor options, potentially limiting user satisfaction. In this study, we explore protocol compliance in an e-cigarette study using a standardized, assigned device with puff time and duration tracking (controlled e-cigarette) and potential limitations that controlled devices and e-liquids can introduce. Methods: In a crossover study, 49 young adult e-cigarette users were recruited using convenience sampling and assigned a controlled e-cigarette device and flavored or unflavored e-liquids on standardized protocols. E-cigarette use frequency (number of puffs per day, collected from the device) and serum cotinine levels were obtained at each of three study visits over 3 weeks. The correlation of cotinine and e-cigarette use over the preceding week was calculated at each study visit. Results: Correlation of nicotine intake, as measured by serum cotinine, and puff time, as measured by puffs count and duration from the e-cigarette device, as an indicator of study protocol compliance, substantially declined after the first week of the study and were no longer correlated in the remaining study weeks ( R 2 = 0.53 and p ≤ .01 in week 1, R 2 < 0.5 and p > .05 for remaining weeks). Conclusions: There is an emerging need for controlled e-cigarette exposures studies, but low compliance in the use of assigned devices and e-liquids may be a limitation that needs to be mitigated in future studies. Implications: This study is the first to analyze compliance with instructions to use a standardized e-cigarette device with puff time and duration tracking (controlled e-cigarette) across all subjects and an assigned e-liquid flavor over a 3-week period. We find that protocol compliance, as measured by correlations between e-cigarette use measures and cotinine levels, was only achieved in the first week of the study and declined thereafter. These findings indicate that the assignment of a study device and instruction to only use the study device with assigned e-liquid flavor may not be sufficient to ensure participant compliance with the study protocol. We suggest that additional measures, including behavioral and biological markers, are needed to ensure sole use of the study e-cigarette and e-liquid and to be able to interpret results from controlled e-cigarette studies.